ENGLISH TEACHER'S STRATEGIES IN TEACHING STUDENTS WITH HEARING IMPAIRMENT AT SMP LUAR BIASA YPAC - Mulkiah F.H. Tambunal; Anwar Ismail (Jurnal Bilingual, 2023)
This research aimed to identify English teachers' strategies in teaching students with hearing impairment and the challenges which the teacher faced in classroom practices. The research method used is qualitative with a case study approach, The subject of this research was an English teacher at SMPLB YPAC. The data were collected by using observation checklist and interview. The result of research showed that there are two strategies used by teachers at SMPLB YPAC grade 8th, namely the manual method which has two basic components, namely sign language and finger spelling and the oral method, namely lip reading or speech reading. Implementing the strategy, there are challenges faced by teachers. The challenges are that first, students sometimes have difficulty understanding words and teachers sometimes need to repeat words or write them down. Second, the limited vocabulary of students and how to overcome them with the teacher needing to explain the definition and provide examples with the media. Third, the teacher did not push students to do exactly what the teacher says. Last, the need for repetition in delivering material with a long duration compared to regular students and the ability of the teacher to remain patient with students is very necessary in answering the last challenge.